The impact of cyber dating abuse on self-esteem: The mediating role of emotional distress - Kaitlin Hancock; Haley Keast; Wendy Ellis (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2017)
This study examined how emotional distress mediated the relationship between cyber dating abuse and self-esteem. Participants were 155 undergraduate students (105 females; 50 males) ranging from 17 to 25 years old (M = 19.38, SD = 1.65) with dating experience and a minimum relationship duration of 3 months. Self-report assessments of cyber dating abuse, self-esteem, and emotional distress from the relationship were completed. Mediation analysis using multiple regressions revealed a full mediation model. Cyber dating abuse predicted lowered self-esteem and greater emotional distress. However, when emotional distress was entered as a predictor of self-esteem, cyber dating abuse became non-significant, indicating full mediation. Early-onset of dating was also a risk factor for cyber dating abuse and emotional distress. Few gender differences were evident. These findings add to the growing body of evidence on the negative effects of cyber dating abuse and suggest that distressing emotional reactions may underlie the deleterious consequences of this form of abuse.